ÍNDICE DE DESENVOLVIMENTO SUSTENTÁVEL PARA MUNICÍPIOS: UMA ANÁLISE NA REGIÃO CANTUQUIRIGUAÇU -PR / SUSTAINABLE DEVELOPMENT INDEX FOR MUNICIPALITIES: AN ANALYSIS IN THE CANTUQUIRIGUAÇU/PR REGION IN BRAZIL - Kasper, Karen Alice; Stoffel, Janete (Informe GEPEC, 2023)
Este trabalho tem como objetivo identificar e analisar o nível de desenvolvimento sustentável dos municípios que constituem a Região da Cantuquiriguaçu/PR. Para tal é utilizado o Índice de Desenvolvimento Sustentável para Municípios (IDSM). O indicador é calculado seguindo a metodologia de Martins e Cândido (2008). São efetuados os cálculos do índice para seis dimensões: social, demográfica, econômica, político-institucional, ambiental e cultural. São utilizadas sessenta e sete variáveis distribuídas nestas dimensões. Em cada dimensão os resultados são apresentados de forma individual para os vinte municípios e é calculada a média da região. Neste ínterim nas dimensões demográfica, econômica, político institucional, ambiental e cultural a média do IDSM para a região está no nível alerta. Apenas na dimensão social o índice é aceitável. Em consequência, a região apresenta um índice de sustentabilidade no nível alerta. Abstract: This article aimed to identify and analyze the level of sustainable development of the municipalities comprising the Cantuquiriguaçu/PR Region. The Sustainable Development Index for Municipalities (SDIM) was used for this purpose. The index was calculated following the methodology of Martins and Cândido (2008). The calculations were performed for six dimensions: social, demographic, economic, political-institutional, environmental, and cultural. Sixty-seven variables distributed along these dimensions were used. In each dimension the results were presented individually for the twenty municipalities and the average for the region was calculated. Meanwhile, regarding the demographic, economic, political, institutional, environmental and cultural dimensions, the average SDIM for the region is at the alert level. Only in the social dimension is the index acceptable. Consequently, the region presents a sustainability index at the alert level.